Synthesis of PLGA nanoparticles containing Auraptene and evaluation of their anti-cancer effects - Suha Lefta Bedan; Ali Es-haghi; Hadi Zare-Zardini (Nanomedicine Journal)
Objective(s): Cancer remains a leading cause of mortality globally, necessitating novel and effective therapies. Nanotechnology, particularly poly (lactic-co-glycolic acid) (PLGA) nanoparticles, offers promising potential for safe and effective delivery of therapeutic agents due to their biocompatibility, biodegradability, and tunable release properties. This study aimed to synthesize PLGA nanoparticles loaded with auraptene (Aur-PLGA-NPs) and evaluate their anti-cancer effects.Materials and Methods: Aur-PLGA-NPs were synthesized and characterized using particle size analyzer, transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR). Cytotoxic effects were assessed against HT-29 colon cancer cells and human umbilical vein endothelial cells (HFF) as normal controls. Apoptotic mechanisms were investigated through 4,6-diamidino-2-phenylindole (DAPI) staining, flow cytometry, and gene expression analysis of caspase-3, caspase-9, and BAX.Results: Spherical nanoparticles with an average size of 185 nm were successfully synthesized. Aur-PLGA-NPs exhibited higher cytotoxicity against HT-29 cancer cells compared to HFF normal cells. Furthermore, Aur-PLGA-NPs significantly enhanced the expression of apoptotic genes caspase-3, caspase-9, and BAX in HT-29 cells.Conclusion: The increased cytotoxicity of Aur-PLGA-NPs against cancer cells suggests their potential as anti-cancer agents. However, further studies are needed to evaluate their effects on other cancer cell lines and elucidate the underlying anti-cancer mechanisms.